Intracellular disposition and metabolism of fluorescently-labeled unmodified and modified oligonucleotides microinjected into mammalian cells. - Fisher, T L (1993)
The intracellular distribution and metabolism of microinjected fluorescently-labeled oligonucleotides (ODNs) have been evaluated using confocal fluorescence microscopy. Fluorescent phosphodiester ODNs, microinjected into the cytoplasm of mammalian cells, rapidly accumulate within the nucleus; the fluorescence disappears with a half-life of 15-20 minutes. Microinjected fluorescent phosphorothioate ODNs remain in the nucleus for more than 24 hours. The persistence of fluorescence depends on the length of the ODN. Modification of the 3' end of phosphodiester ODNs does not significantly slow the rapid disappearance of fluorescence, although certain 3' modifications localize ODNs into the cytoplasm. Using specially designed ODNs, endonuclease activity is demonstrated to exist in the cytoplasm and nucleus. Modification of the 2' position of the ribose rings of a fluorescent phosphodiester oligodeoxynucleotide with O-methyl or O-allyl does not alter its intracellular distribution; however, the 2'-O-allyl modification stabilizes the persistence of fluorescence more than 60-fold compared to the 2'-deoxy control. Thus, the experiments indicate that somatic cells contain nucleolytic activities which degrade microinjected ODNs; however, chemical modification can dramatically circumvent this process.